Meningkatkan Kemampuan Motorik Kasar Dalam Gerakan Variasi Melalui Permainan Gambar Anak Usia 4-5 Tahun di Taman Kanak-Kanak Santa Theresia I Pangkalpinang - Bernadet Sepryyana (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The low gross motor skills of children aged 4-5 years in class A2 of Santa. Theresia I Pangkalpinang is the impetus for this research. Alternative solutions offered by researchers are using image media with the aim of increasing gross motor and children's interest in learning. Through these learning activities, students become active and the teaching and learning process is fun so that learning objectives are achieved. The corrective action is carried out for two weeks with stages, namely preparing the implementation of action and observation, reflection and evaluation then the data obtained is analyzed descriptively. In collecting data, the techniques used are observation and documentation techniques; Observation is used to see directly to students how to develop Gross Motor Skills in Variation Movement Through Picture Games for 4-5 Year Old Children at Santa Theresia I Pangkalpinang Kindergarten, The documentation technique is used to obtain data regarding the description of the existence of the object under study. In addition, to complement the data from observations and interviews. Based on the results of the improvement, it can be concluded that the method of using image media can attract kindergarten students' interest in learning from 52% to 80% and involve their cognitive, affective, and psychomotor activeness in teaching and learning process activities in the classroom. Keywords: Gross motor, variation movement, picture game